An Improved Analytical Method for the Determination of Brown FK in Food using HPLC. (17th March 2018) - Park, Ju-Hee; Kim, Young-Woo; Jeong, Yeon-Seong; Suh, Hee-Jae; Chun, Hyang-Sook; Lee, Gun-Young; Lim, Ho-Soo; Lee, Chan
Abstract: In this study, an improved analytical method for the detection of the colorant Brown FK in foods using high-performance liquid chromatography was developed. The method, which employed an RC-C18 column and diode array detection at 254 nm with sodium acetate solution and methanol as mobile phases, exhibited good linearity ( R 2 = 1.0), and its limits of detection and quantification were determined to be 0.06 and 0.19 μg/mL, respectively. The precision was found to be 0–1.2% and the accuracy was between 86.5% and 94.8%. Liquid chromatography-tandem mass spectrometry was also performed to identify Brown FK in peaks. The pretreatment method was optimized for three different food sample groups, i.e., seafood, noodles and other, affording recoveries of 86.5–92.8%, 90.8–94.8% and 90.0–92.3%, respectively. In addition, inter-laboratory testing was also conducted to check the precision.